2017
DOI: 10.3390/nu9040379
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status, Muscle Strength and Physical Performance Decline in Very Old Adults: A Prospective Study

Abstract: Mixed reports exist about the role of 25-hydroxyvitamin D (25(OH)D) in muscle ageing and there are few prospective studies involving the very old (aged ≥ 85) who are at highest risk of low 25(OH)D, loss of muscle mass and strength, and physical performance decline. In the Newcastle 85+ Study (n = 845), we aimed to determine the association between 25(OH)D season-specific quartiles (hereafter SQ1–SQ4), grip strength (GS) and physical performance decline (Timed Up-and-Go Test, TUG) over 5 years using mixed model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 57 publications
(155 reference statements)
1
64
0
1
Order By: Relevance
“…27,28 We could not evaluate biomarkers of serum vitamin D related to muscle strength, in our participants. 29 Future exercise and nutritional supplementation studies will need to include measurements of vitamin D status. There is current evidence of a positive effect of a supplementation of approximately 2500-2800 mg of leucine in increasing the rate of muscle protein synthesis in healthy older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 We could not evaluate biomarkers of serum vitamin D related to muscle strength, in our participants. 29 Future exercise and nutritional supplementation studies will need to include measurements of vitamin D status. There is current evidence of a positive effect of a supplementation of approximately 2500-2800 mg of leucine in increasing the rate of muscle protein synthesis in healthy older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A relevant number of epidemiological studies have suggested the potential role of vitamin D in order to maintain or improve muscle strength and function, physical performance and preserve independence in older people [14,15]. Although, the biological role of vitamin D on skeletal muscles function has been widely investigated [16,17], in the past years the expression of VDR on skeletal muscle cells has been questioned.…”
Section: Role Of Vitamin D On the Skeletal Muscle Systemmentioning
confidence: 99%
“…Many prospective studies have examined the vitamin D role in muscle strength and physical performance in older adults [34,35,[38][39][40][41][42], although they differ in participants characteristics and type of muscle strength assessment. Several studies have shown as in older people, that serum levels of vitamin D are independently related to the loss of muscle mass and muscle strength decline [34,64], more in men than in women [17,65], suggesting that older people with vitamin D deficiency are extremely exposed to develop sarcopenia. A prospective study published in 2017 has shown that low circulating vitamin D levels are associated to an accelerated loss of muscle strength (measured as hand grip strength) in men ≥ 85 years; conversely, no significant differences have been found in physical performance, assessed by TUG, over time [66].…”
Section: Vitamin D Deficiency and Sarcopeniamentioning
confidence: 99%
“…Previous studies have demonstrated a positive relationship between 25(OH)D levels and HGS in old males. 12,13,23,24 However, no association between serum 25(OH)D concentration and HGS was found in a study of 1219 males aged 30-79 years 14 and another study of males and females aged 20-76 years. 15 The reason for these conflicting findings may stem from the age range of participants being very broad.…”
Section: Discussionmentioning
confidence: 99%
“…However, results in the literature have not reached a consensus. Among older adults, many of the studies have reported a positive relationship between vitamin D status and HGS, 12,13 but this result cannot be found in the studies performed in participants with a broad age range. 14,15 Since HGS begins attenuating after 50 years of age, 8 we hypothesized that vitamin D is more beneficial to the maintenance of HGS in adults aged above 50 years than adults that are younger.…”
Section: Introductionmentioning
confidence: 92%